Legal Status of Cryptocurrency in Indonesia and Legal Analysis of the Business Activities in Terms of Cryptocurrency - Chang, Soonpeel Edgar (Brawijaya Law Journal, 2019)
Indonesia’s recent development in legal policy toward cryptocurrency is pertinent to ask whether this new investment market has any more risk to throw over Indonesia than how to protect the existing variable parties by overall structural formation. This tendency has prevented the government to implement the machinery of more fundamental keynote of policy. Against this backdrops, this research first analyzes the existing laws and regulations to examine the current legal status of virtual currency in Indonesia with the method of conceptual analysis. Despite the Government’s skeptical stance about economic soundness that cryptocurrency market leads, however, how to protect the various parties in the existing market is a different issue which still needs an urgent attention from policy makers, legal practitioners, judiciary and academic researchers. Therefore, this paper further studies the relevant laws and regulations governing the actual operation of cryptocurrency exchange in Indonesia to discuss the more practical aspects by interviewing an Indonesian cryptocurrency exchange and professional lawyers at Dentons HPRP. Subsequently, the most worrisome legal risks in the industry are diagnosed by interviewing a global cryptocurrency exchanges. This study concludes that BAPPEBTI Regulation No. 5 of 2019 cannot be the good answer to minimize the risk and will only harm bona fide market participants without a good-standing authority.